Manajemen Kurikulum Pendidikan Islam di SDN Neglasari 1 Kota Tangerang - Amalia, Rizki (INTIFA: Journal of Education and Language, 2024)
ABSTRACK This research was conducted as an effort to determine the implementation of Islamic education curriculum management at SDN Neglasari 1 Tangerang. The aim of this research is to determine the implementation of curriculum management in Islamic Education at SDN Neglasari 1 Tangerang. This type of research is qualitative research with a descriptive approach. The data collection process is through interviews, observation and documentation. The results of this research explain that the implementation of curriculum management at SDN Neglasari 1 Tangerang is in accordance with the indicators of Islamic religious education curriculum management, carried out as follows: 1) Analysis of Islamic education curriculum management, 2) Islamic education curriculum planning process 3) organization of the Islamic education curriculum, 4 ) Implementation of the Islamic education curriculum, 5) Evaluation of the Islamic education curriculum. It was concluded that in general SDN Neglasari 1 Tangerang had implemented Islamic education curriculum management in accordance with the implementation of curriculum management. ABSTRACK Penelitian ini dilakukan sebagai usaha untuk mengetahui penerapan manajemen kurikulum pendidikan Islam di SDN Neglasari 1 Kota Tangerang. Tujuan dari penelitian ini adalah untuk mengetahui penerapan manajemen kurikulum di Pendidikan Islam di SDN Neglasari 1 Kota Tangerang. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan deskriptif. Proses pengumpulan datanya melalui wawancara, dan observasi. Hasil penelitian ini menjelaskan bahwa implementasi manajemen kurikulum di SDN Neglasari 1 Kota Tangerang sudah sesuai dengan indikator manajemen kurikulum pendidikan agama Islam, terlaksana seperti halnya: 1) Analisis manajemen kurikulum pendidikan Islam, 2) proses Perencanaan Kurikulum pendidikan Islam 3) perorganisasian kurikulum pendidikan Islam, 4) Pelaksanaan kurikulum pendidikan Islam, 5) Evaluasi kurikulum pendidikan Islam. Disimpulkan bahwa secara umum SDN Neglasari 1 Kota Tangerang telah melaksanakan manajemen kurikulum pendidikan Islam sesuai dengan implementasi manajemen kurikulum.